VARS2-linked mitochondrial encephalopathy: two case reports enlarging the clinical phenotype - Chiara Begliuomini; Giorgio Magli; Maja Di Rocco; Filippo M. Santorelli; Denise Cassandrini; Claudia Nesti; Federica Deodato; Daria Diodato; Susanna Casellato; Delia M. Simula; Veronica Dessì; Anna Eusebi; et al. (BMC, 2019)
Abstract Background Mitochondrial respiratory chain consists of five complexes encoded by nuclear and mitochondrial genomes. Mitochondrial aminoacyl-tRNA synthetases are key enzymes in the synthesis of such complexes. Bi-allelic variants of VARS2, a nuclear gene encoding for valyl-tRNA (Val-tRNA) synthetase, are associated to several forms of mitochondrial encephalopathies or cardiomyoencephalopathies. Among these, the rare homozygous c.1100C > T (p.Thr367Ile) mutation variably presents with progressive developmental delay, axial hypotonia, limbs spasticity, drug-resistant epilepsy leading, in some cases, to premature death. Yet only six cases, of which three are siblings, harbouring this homozygous mutation have been described worldwide. Case presentation Hereby, we report two additional cases of two non-related young girls from Sardinia, born from non-consanguineous and healthy parents, carrying the aforesaid homozygous VARS2 variant. At onset both the patients presented with worsening psychomotor delay, muscle hypotonia and brisk tendon reflexes. Standard genetic tests were normal, as well as metabolic investigations. Brain MRI showed unspecific progressive abnormalities, such as corpus callosum hypoplasia (patient A) and cerebellar atrophy (patient A and B). Diagnosis was reached by adopting massive parallel next generation sequencing. Notably clinical phenotype of the first patient appears to be milder compared to previous known cases. The second patient eventually developed refractory epilepsy and currently presents with severe global impairment. Because no specific treatment is available as yet, both patients are treated with supporting antioxidant compounds along with symptomatic therapies. Conclusions Given the paucity of clinical data about this very rare mitochondrial encephalopathy, our report might contribute to broaden the phenotypic spectrum of the disorder. Moreover, noteworthy, three out of five pedigrees so far described belong to the Northern Sardinia ethnicity.